Transformation of Islamic Criminal Law in the National Legal System: A Comparative Study of Narcotics Crime Regulation Reform Models in Indonesia, Malaysia and Sudan - Daipon, Dahyul; Hasibuan, Pendi; Ritonga, Zulkarnaen; Zulkifli, Zulkifli; Muhammad, Fajar Alief (SPT. haria Journal and Education Center Publishing, 2026)
This study examines the transformation of Islamic criminal law across three Muslim-majority countries Indonesia, Malaysia, and Sudan within the context of narcotics regulation. Employing a qualitative comparative approach that integrates legal document analysis, expert interviews, and secondary data on drug abuse prevalence, this study identifies structural differences, points of consistency, and key factors influencing regulatory effectiveness. The results yield a Sharia-based regulatory framework model that can be adapted by other nations with similar Islamic legal systems. These findings contribute to the literature on Islamic criminal law and offer an empirical foundation for more coherent and sustainable narcotics policy reform.